IBARRA, Antonio, Álvaro ALCÁNTARA y Fernando JUMAR (coords.), Actores sociales, redes de negocios y corporaciones en Hispanoamérica, siglos XVII-XIX, México, Bonilla Artigas Editores/Universidad Nacional Autónoma de México, Pública Histórica 12, 2018, 344 (Tzintzun, Revista de Estudios Históricos, 2022)
-